Pineapple (ananas comosus l.) peels as corrosion inhibitor for carbon steel in hydrochloric acid solution - Jenit Gervase, Peter Lidadun (2014)
Corrosion in steel has been identified as one of the major problem in chemical industry which responsible for substantive plant shutdown that contributes to high maintenance costs especially in pipelines system. In addition contamination of products and process streams, and external corrosion leaks due to internal corrosion failures can create unfortunate safety, manpower and environmental jeopardy. In order to overcome this problem, certain techniques have been applied and one of the most practical ways is using inhibitor to protect metals against corrosive environment. Commercial and synthetic inhibitors are commonly used and have been proved to be effective in inhibiting corrosive attack on metal but most of these inhibitors are toxic and expensive thus become major setback. To alleviate this issues, researcher were focused on eco-friendly corrosion inhibitor using natural and biodegradable compound which is effective, low cost and low environmental impact. Pineapple peels is cheap abundant resource in Malaysia, and hence this work presents corrosion inhibitor studies using pineapple (Ananas comosus L.) peels extract. Corrosion rates were determined using weight loss method for three parameters; concentration of inhibitor, acid concentration and exposure time. Pineapple peels extract was analysed by Gas Chromatography-Mass Spectrometer to determine the chemical composition in the extracts which has the inhibition functions. The extract proved to contains oleic acid and octadenoic acid which have carbonyl group and double bonds. These characteristics mostly found in plant extract which can inhibit corrosion The weight loss method was conducted according to the standard provided by ASTM. The corrosion rate of steel was found to be dependent on acid concentration and also extract concentration. Another factor is exposure time which contributes to the value of corrosion rate. Results from this work may be useful to study the efficiency of this inhibitor using more parameters as this will become alternative for commercial inhibitor.